Protein engineering and preclinical development of a GM‐CSF receptor antibody for the treatment of rheumatoid arthritis. (18th December 2012) - Minter, RR; Cohen, ES; Wang, B; Liang, M; Vainshtein, I; Rees, G; Eghobamien, L; Harrison, P; Sims, DA; Matthews, C; Wilkinson, T; Monk, P; et al.
Abstract : Background and Purpose: For antibody therapies against receptor targets, in vivo outcomes can be difficult to predict because of target‐mediated clearance or antigen 'sink' effects. The purpose of this work was to engineer an antibody to the GM‐CSF receptor α (GM‐CSFRα) with pharmacological properties optimized for chronic, s.c. treatment of rheumatoid arthritis (RA) patients. Experimental Approach: We used an in silico model of receptor occupancy to guide the target affinity and a combinatorial phage display approach for affinity maturation. Mechanism of action and internalization assays were performed on the optimized antibody in vitro before refining the modelling predictions of the eventual dosing in man. Finally, in vivo pharmacology studies in cynomolgus monkeys were carried out to inform the predictions and support future clinical development. Key Results: Antibody potency was improved 8600‐fold, and the target affinity was reached. The refined model predicted pharmacodynamic effects at doses as low as 1 mg kg −1 and a study in cynomolgus monkeys confirmed in vivo efficacy at 1 mg kg −1 dosing. Conclusions and Implications: This rational approach to antibody drug discovery enabled the isolation of a potent molecule compatible with chronic, s.c. self‐administration by RA patients. We believe this general approach enables the development of optimal biopharmaceuticals.